Associations of Leukocyte-Derived Chemotaxin-2 (LECT2) with Insulin Resistance and Metabolic Syndrome in Type 2 Diabetes: A Cross-Sectional Study - Sha Y; Lu J; Jin R; Li L; Zhang M (Diabetes, Metabolic Syndrome and Obesity)
Yujing Sha,* Jiaping Lu,* Rui Jin, Lian Li, Min Zhang Department of Endocrinology, Qingpu Branch of Zhongshan Hospital Affiliated to Fudan University, Shanghai, 201700, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Zhang, Department of Endocrinology, Qingpu Branch of Zhongshan Hospital Affiliated to Fudan University, N0.1158 of East Gongyuan Road, Qingpu District, Shanghai, 201700, People’s Republic of China, Tel +86 18116016187, Email 18116016187@163.comObjective: Leukocyte-derived chemokine-2 (LECT2) is a novel neutrophil chemokine synthesized by the liver. This research aimed to investigate the potential link between LECT2 levels and metabolic syndrome (MetS) as well as insulin resistance (IR) in patients with type 2 diabetes mellitus (T2D). The results could offer fresh perspectives on the diagnosis and therapeutic strategies for T2D and associated metabolic disorders.Methods: A cross-sectional study was conducted on 148 T2D patients, including 90 with MetS and 58 without MetS. The diagnosis of MetS was based on the standardized guidelines established by the International Diabetes Federation. IR was assessed via HOMA-IR, with a cutoff of ≥ 2.69. Serum LECT2 levels were measured using ELISA.Results: In T2D patients, individuals with MetS exhibited significantly higher LECT2 levels than the non-MetS group (1.73± 0.31 ng/mL vs 1.55± 0.33 ng/mL, P< 0.05). In addition, LECT2 concentrations were significantly elevated in the IR group compared to the N-IR group (1.75 ± 0.33 ng/mL vs 1.61± 0.32ng/mL, P< 0.05). Higher LECT2 levels were linked to increased metabolic dysfunction, as reflected by elevated FPG, FINS, HOMA-IR, and TG levels. Multivariable logistic regression analysis demonstrated that, after adjusting for multiple confounding factors, LECT2 still exhibits a significant association with the occurrence of MetS (OR=8.48, P=0.01).Conclusion: LECT2 concentrations were elevated in T2D patients combined with MetS and were significantly related to IR. These results indicate that LECT2 could contribute to the pathogenesis of T2D accompanied by MetS, and LECT2 may represent a promising therapeutic target for MetS and its related metabolic disturbances.Keywords: leukocyte-derived chemokine-2, metabolic syndrome, diabetes mellitus, type 2, insulin resistance